Unfavourable effects of medically indicated oral anticoagulants on survival in idiopathic pulmonary fibrosis - Kreuter, Michael (The European respiratory journal, 2016)
Procoagulant and antifibrinolytic activity has been associated with idiopathic pulmonary fibrosis (IPF); however, investigation of anticoagulant therapy in IPF has suggested deleterious effects. This post hoc analysis evaluated the effect of medically indicated anticoagulation on mortality and other clinical outcomes in IPF. Patients randomised to placebo (n=624) from three controlled trials in IPF were analysed by oral anticoagulant use. End-points included all-cause and IPF-related mortality, disease progression, hospitalisation, and adverse events, over 1 year. At baseline, 32 (5.1%) patients randomised to placebo were prescribed anticoagulants for non-IPF indications, 29 (90.6%) of whom received warfarin. Unadjusted analyses demonstrated significantly higher all-cause and IPF-related mortality at 1 year in baseline anticoagulant users versus nonusers (15.6% versus 6.3%, p=0.039 and 15.6% versus 3.9%, p=0.002, respectively). In multivariate analyses, baseline use of anticoagulants was an independent predictor of IPF-related mortality (hazard ratio 4.7, p=0.034), but not other end-points. Rates of bleeding and cardiac events did not differ significantly between groups. In an exploratory analysis, anticoagulant use at any time during the study was an independent predictor of all end-points. This post hoc analysis suggests that anticoagulants used for non-IPF indications may have unfavourable effects in IPF patients. Future studies are needed to explore this relationship further. Tweetable abstract ERSpublications click to tweetAnticoagulant use for medically indicated comorbidities may have unfavourable effects in IPF http://ow.ly/XZC9j